Case report: A case of anti-glycine receptor encephalomyelitis triggered by post-transplant or COVID-19 infection? - Zhang, Zhengxue; Zhang, Xiang; Dai, Mingming; Wu, Yingying; You, Yong (Frontiers in Neurology, 2024)
Even though long-term immunosuppressant drugs (ISD) are employed to inhibit immune system activity, enhancing graft functionality and patient survival in solid organ transplantation (SOT), these transplants often lead to immune complications, with post-transplant autoimmune diseases of the central nervous system (CNS) being uncommon. Here, we detail the case of a 66-year-old woman who underwent a renal transplantation 8 months prior, who was admitted with subacute onset of encephalomyelitis, accompanied by headaches, paraplegia, weakness, vomiting, and abdominal pain, with a positive COVID-19 nasopharyngeal swab test 1 month before admission. MRI scans of the brain revealed multiple lesions in the white matter of the bilateral deep frontal lobe, the left temporal lobe and insula lobe. Additionally, there were multiple short segment lesions in the spinal cord and subdural hematoma at T1, T6-T7 posterior. The serum revealed a positive result for GlyR-IgG. Following the administration of corticosteroid and intravenous immunoglobulin, there was a significant improvement in the patient’s symptoms within 2 weeks, and her brain MRI showed a reduction in the lesion. Despite its rarity, we believe this to be the inaugural documentation of anti-GlyR encephalomyelitis occurring during renal transplantation. A full panel of antibodies for autoimmune encephalomyelitis is the key leading to the diagnosis.